Smartphone sleep technology: health apps during covid-19 to mitigate psychosocial stress among children and adolescents - Cathy Mae Dabi Toquero (CV Rezki Media, 2021)
Children and adolescents are prone to physical fatigue and psychosocial anxiety because of the ongoing social distancing and sleep deprivations due to the long exposure to digital technology usage during the covid-19 pandemic. This scenario of sleep deprivation affects their educational endeavors and health quality. Through the use of smartphones as a sleep technology approach in mental health, this article reviews relevant literature concerning the mobile health applications for sleep hygiene among children and adolescents. It provides insight into smartphone sleep technology utilization that can alleviate the psychosocial stress and mental health issues that children and adolescents can experience amid the pandemic. The author stressed that the collaboration among health practitioners, educators, and researchers are also pertinent to strengthen health measures and to conduct evidence-based research on digital health interventions. The scientific results can increase smartphone-based sleep applications' monitoring as health interventions for children and adolescents to practice sleep hygiene. Future investigation should also examine and assess the effectiveness of smartphone sleep technologies for sleep quality and mental health outcomes.